EFISIENSI BEBERAPA MODEL TUNGKU - Djeni Hendra; Gustan Pari (Jurnal Penelitian Hasil Hutan, 1993)
The result of investigation of cook stove designs from Palembang, Yogyakarta and Bogor is reported in this paper. Fuel wood used were : Acacia mangium, Acacia auriculiformis and Leucaena glauca.The result shows that the dry wood consumption for high power phase ranges from 0,31 - 0,43 kg, dry wood consumption for low power phase ranges from 0,01 - 0,42 kg, high power phase from 6,12 - 13,23 KW, low power phase from 0,17- 2,98 KW, wood standard consumption from 0,20 - 0,25 kg wood/kg water, flexibility from 2.51 - 21,86 and efficiency ranges from 12,42 - 24,79 %.